Effect of ozone therapy on autogenous bone graft healing in calvarial defects: a histologic and histometric study in rats. (3rd March 2013) - Ozdemir, H.; Toker, H.; Balcı, H.; Ozer, H.
Abstract : Aim: The purpose of this study was to analyze histologically the effect of ozone therapy in combination with autogenous bone graft on bone healing in rat calvaria. Methods: Critical size defects were created in calvaria of 27 male Wistar rats. The animals were divided into three groups of nine animals each: autogenous bone graft group ( n = 9); autogenous bone graft with ozone therapy group (80%, 30 s 3 d for 2 wk, n = 9); non‐treatment (control) group ( n = 9). Animals were killed after 8 wk. Histomorphometric assessments, using image analysis software, and histological analyses were performed. Primary outcome was total bone area. Secondary outcomes (osteoblast number, new bone formation) were also measured. Results: Histomorphometrically, the total bone area in the autogenous bone graft with ozone therapy group (9.3 ± 2.2) were significantly higher than that of the autogenous bone graft group (5.1 ± 1.8) ( p < 0.05). Also, the ozone therapy group significantly increased the percentage of total bone area compared to the autogenous bone graft group ( p < 0.05). The osteoblast number significantly increased in the autogenous bone graft with the ozone therapy group (58 ± 12.3) compared to the autogenous bone graft group (9.3 ± 3.5) ( p < 0.05). Also, it was observed that autogenous bone graft with ozone therapy group showed significant new bone formation when compared to the autogenous bone graft group ( p < 0.05). Conclusion: Ozone therapy enhances new bone formation by autogenous bone graft in the rat calvarial defect model.